2014
DOI: 10.1089/scd.2013.0632
|View full text |Cite
|
Sign up to set email alerts
|

Netrin-1 Induces MMP-12-Dependent E-Cadherin Degradation Via the Distinct Activation of PKCα and FAK/Fyn in Promoting Mesenchymal Stem Cell Motility

Abstract: Netrin-1 (Ntn-1) is a potent inducer of neuronal cell migration; however, its molecular mechanism that guides the migratory behavior of stem cells has not been characterized. In this study, we investigate the role of Ntn-1 in promoting the motility of human umbilical cord blood-derived mesenchymal stem cells (UCB-MSCs) and its related signaling pathways. Ntn-1 (50 ng/mL) significantly increased motility of UCB-MSCs, which was inhibited by blocking antibodies for deleted in colorectal cancer (DCC) and integrin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
34
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 48 publications
(42 reference statements)
4
34
1
1
Order By: Relevance
“…Because PKCα is a conventional PKC that requires both Ca 2+ and DAG for activation [46], Ca 2+ binding to the C2 domain of matured PKCα initiates translocation to the membrane. And several studies have reported that PKCα activation plays a crucial role in the migration of cord-bloodderived stem cells [47,48]. Related to this, OA-induced PKCα phosphorylation was inhibited by a GPR40 antagonist, GW1100, and controlled by Gα q , but not by Gα i or Gα 12 .…”
Section: Discussionmentioning
confidence: 91%
“…Because PKCα is a conventional PKC that requires both Ca 2+ and DAG for activation [46], Ca 2+ binding to the C2 domain of matured PKCα initiates translocation to the membrane. And several studies have reported that PKCα activation plays a crucial role in the migration of cord-bloodderived stem cells [47,48]. Related to this, OA-induced PKCα phosphorylation was inhibited by a GPR40 antagonist, GW1100, and controlled by Gα q , but not by Gα i or Gα 12 .…”
Section: Discussionmentioning
confidence: 91%
“…Thus, migration is considered to be an important factor of MSC-induced wound healing. E-cadherin degradation by netrin pretreatment enhances migratory ability of hUCB-MSCs [50]. The reduction of E-cadherin expression during cell migration can be controlled by epigenetic transcriptional regulation and post-transcriptional modification of transcription for the CDH1 gene [51].…”
Section: Discussionmentioning
confidence: 99%
“…E-cadherin is frequently downregulated during carcinoma metastasis (26). Loss of E-cadherin facilitates the initial invasive behavior of cancer (27). MMPs promote cell invasion and migration in several types of cancers, such as osteosarcoma, prostate, lung, colon and pancreas cancer (28).…”
Section: Discussionmentioning
confidence: 99%